PENGARUH PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN PENDEKATAN SAINTIFIK TERHADAP BERPIKIR KRITIS, KECERDASAN EMOSIONAL DAN KOLABORASI - Desy Fitriani; Jailani Jailani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The aims of this study were 1) to analyze the effect of  Student Team Achievement Division (STAD) cooperative learning with a scientific approach to critical thinking skills; 2) analyze the effect of  STAD cooperative learning with  scientific approach to emotional intelligence; 3) analyze the effect of  STAD cooperative learning with a scientific approach to collaboration. This type of research was pre-experimental through a one-group pretest-posttest design. The subject of this study was class VII B MTs Terpadu Berkah Palangka Raya with a total of 29 students. Data collection techniques in this study were tests, questionnaires and observation. The data analysis technique used is the paired t-test. Based on the research results, it was found that the STAD type of cooperative learning with a scientific approach has a positive effect on being able to improve critical thinking skills, emotional intelligence and collaboration.